Effect of strontium doping on the structural, morphological, and dielectric properties of PZT ceramics - Silva, Margarete S.; Dias, Rafael G.; Souza, Eliane F.; Cilense, Mário [UNESP]; Zaghete, Maria A. [UNESP]; Cavalheiro, Alberto A. (Trans Tech Publications, 2016)
Strontium-modified lead zirconate titanate ceramics was prepared by the polymeric precursor method. The effect of Pb(II) substitution by Sr(II) in A site of the perovskite structure at molar percentages of 0.0, 0.2, 0.4 and 0.6 mol% was investigated through XRD and Rietveld method. The increasing of strontium amount displaces the morphotropic phase boundary toward to tetragonal phase and that results can be associated to the tetragonal lattice expansion besides the rhombohedral opposite phenomenon. The effect of strontium substitution on the dielectric properties for sintered ceramics is also investigated and showed the strontium substitution leads to reduction of weight loss and increasing of density for sintered ceramic. The Kc and Tc oscillates as function of ceramic morphology and is not possible to verify the existence of conductive intergrains defects by loss tangent curves. An intrinsic event can be occurring because considerable lattice distortion was verified in tetragonal and rhombohedral structures for powder samples.
Keywords: Microstructure; PZT; Sr-doped